Systematic Literature Review Analisis Kemampuan Gaya Kognitif Field Dependent dan Field Independent dari Hasil Belajar - achilla, Silky; Masrukan; Kharisudin, Iqbal; Zaenuri; Walid (Circle: Jurnal Pendidikan Matematika, 2024)
This research aims to analyze field dependent (FD) and field independent (FI) cognitive style abilities based on learning outcomes through a systematic literature review. Education plays an important role in developing individual potential, where students' cognitive style is one of the determining factors in understanding concepts. Cognitive style refers to the way an individual receives, stores, processes, and presents information. The research method follows the systematic literature review (SLR) stages with a focus on three research questions: (1) educational levels that are often studied, (2) mathematical abilities that are measured, and (3) the influence of gender differences on cognitive styles and learning outcomes. Data was collected from Google Scholar and Mendeley with inclusion criteria from 2015 to 2024. The research results show that the education level most researched is Junior High School (SMP), with the main focus on mathematical problem solving abilities. Additionally, it was found that cognitive style and gender significantly influenced mathematical problem solving abilities, with female students showing advantages in mathematical communication and learning motivation. This research provides insight into the importance of understanding differences in cognitive styles in the learning process and their influence on learning outcomes, and emphasizes the need for teaching strategies that are tailored to students' cognitive needs.